2020
DOI: 10.1371/journal.pone.0230953
|View full text |Cite
|
Sign up to set email alerts
|

Effect of treatment modality and cerebral vasospasm agent on patient outcomes after aneurysmal subarachnoid hemorrhage in the elderly aged 75 years and older

Abstract: We sought to examine whether the effect of treatment modality and drugs for cerebral vasospasm on clinical outcomes differs between elderly and non-elderly subarachnoid hemorrhage (SAH) patients in Japan. Methods We analyzed the J-ASPECT Study Diagnosis Procedure Combination database (n = 17,343) that underwent clipping or coiling between 2010 and 2014 in 579 hospitals. We stratified patients into two groups according to their age (elderly [�75 years old], n = 3,885; non-elderly, n = 13,458). We analyzed the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 45 publications
0
13
1
Order By: Relevance
“…In our study, surgical aneurysm closure was associated with unfavorable outcome and mortality at 12 months only in the older age group. In contrast, most of previous studies have found no differences between surgical and endovascular treatment in the elderly [12,22,25].…”
Section: Comparison With Previous Literaturecontrasting
confidence: 57%
“…In our study, surgical aneurysm closure was associated with unfavorable outcome and mortality at 12 months only in the older age group. In contrast, most of previous studies have found no differences between surgical and endovascular treatment in the elderly [12,22,25].…”
Section: Comparison With Previous Literaturecontrasting
confidence: 57%
“…Although ozagrel has been used in combination with statins in previous clinical studies[ 50 ], most studies assessed only blood glucose or a single blood index. We assessed blood glucose, blood lipids, blood coagulation, ESR, NIHSS score, ADL score, inflammatory factors, and specific indicators, namely, HMGB1, PON-1, and MIF in a comprehensive analysis; we found that the combination of these two drugs has a good effect on blood glucose and blood lipids, reduces nerve injury, and reduces inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Among the studies, 17 of 20 comparative studies and 28 of 39 regression-based studies were conducted in single centers (ESM Table S4). Seven regression-based studies collected data from a large number (i.e., > 30) of centers, including five post hoc analyses of the CONSCIOUS-1 trial [ 45 , 56 , 60 , 61 , 67 ] and two studies based in Japan [ 62 , 73 ].…”
Section: Resultsmentioning
confidence: 99%